A Review of Pain Assessment in Pigs - Ison, Sarah H.; Clutton, R. Eddie; Di Giminiani, Pierpaolo; Rutherford, Kenneth M. D. (Frontiers in Veterinary Science, 2016)
There is a moral obligation to minimize pain in pigs used for human benefit. In livestock production pigs experience pain caused by management procedures, e.g. castration, and tail docking, injuries from fighting or poor housing conditions, “management diseases” like mastitis or Streptococcal meningitis, and at parturition. Pigs used in biomedical research undergo procedures which are regarded as painful in humans, but do not receive similar levels of analgesia, and pet pigs also experience potentially painful conditions. In all contexts, accurate pain assessment is a prerequisite in: a) the estimation of the welfare consequences of noxious interventions; and b) the development of more effective pain mitigation strategies. This narrative review identifies the sources of pain in pigs, discusses the various assessment measures currently available, and proposes directions for future investigation.